Alcohol use disorder and risk of sensitization to environmental allergens in Sub-Continental Asian Indian males. Issue 3 (2nd October 2018) - Kumar, Yashwant; Laxmi, PVM; Minz, Ranjana Walker; Pal, Arnab
Abstract: Alcohol is known to cause elevation of serum total IgE (tIgE). Whether it can predispose to allergic disorders, however, is not clear. To assess whether alcohol can cause sensitization to allergens, we analyzed 100 individuals with alcohol use disorder (AUD) and 50 matched healthy controls. Serum tIgE and specific IgE against environmental allergens were measured. We found 93% of individuals with AUD had raised tIgE compared to only 48% of healthy controls ( p < 0.0001). Sensitization to aeroallergens was noted in 68% drinkers compared to 24% of controls ( p < 0.0001). The degree of sensitization was directly proportional to the amount and duration of alcohol intake. There is a possibility of a link between alcohol abuse and allergic sensitization.